1996
DOI: 10.1002/jlac.199619960904
|View full text |Cite
|
Sign up to set email alerts
|

Diastereo‐ and Enantioselective Synthesis of Lignan Building Blocks by Tandem Michael Addition/Electrophilic Substitution of Lithiated α‐Amino Nitriles to Furan‐2(5H)‐one

Abstract: Starting from chiral α‐amino nitriles (S,S,R/S)‐3, we prepared β‐aroyl‐γ‐butyrolactones (S)‐5 as well as 2,3‐disubstituted γ ‐butyrolactones (S,S)‐ or (R,S,R)‐6 in high yields and with high enantiomeric excesses by conjugate addition to butenolide, followed by protonation, α‐alkylation or α‐aldol addition, respectively. The introduction of one up to three stereogenic centers opens a flexible and highly efficient diastereo‐ and enantioselective route to 2,3‐dibenzylated γ‐butyrolactones 6, which proved to be im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…When this was subjected to FVP at 500 °C, there was almost complete reaction with loss of pivalaldehyde and CO to give, after preparative TLC, the lactone (4S)-4-benzoyltet rahydrofuran-2-one 15 in good yield. This showed good agreement with NMR chemica shift values from the literature and based on its optical rotation [21], the e.e. was 58%.…”
Section: Michael Addition Of Dioxolanone 5 To Butenolide and β-Nitro-...supporting
confidence: 89%
See 1 more Smart Citation
“…When this was subjected to FVP at 500 °C, there was almost complete reaction with loss of pivalaldehyde and CO to give, after preparative TLC, the lactone (4S)-4-benzoyltet rahydrofuran-2-one 15 in good yield. This showed good agreement with NMR chemica shift values from the literature and based on its optical rotation [21], the e.e. was 58%.…”
Section: Michael Addition Of Dioxolanone 5 To Butenolide and β-Nitro-...supporting
confidence: 89%
“…[α] D −11.3 (c = 0.56, CHCl 3 ), [lit. [21] 3.2.3. Preparation of (2S,5S)-2-t-Butyl-5-(1 -(4-methoxyphenyl)-2 -nitroethyl)-5-phenyl-1,3-dioxolan-4-one 6a/6b [11] To a solution of LDA (22 mmol) in dry THF (100 cm 3 ) at −78 • C, a solution of (2S,5S)-2-t-butyl-5-phenyl-1,3-dioxolan-4-one 5 (4.40 g, 20 mmol) in dry THF (30 cm 3 ) was added slowly by syringe.…”
Section: Preparation and Reactions Of Dioxolanone Michael Addition Pr...mentioning
confidence: 99%
“…The γ-aroylated products 79 were formed in good overall yields (47−71%) and excellent enantioselectivities (90-≥96% ee) following a mild Lewis acid promoted hydrolysis reaction of the amino nitrile function within the Michael adducts 78 . Subsequent studies revealed that cyclic enones and α,β-unsaturated lactones could be tolerated well in the protocol . Furthermore, a tandem Michael addition/alkylation reaction using an analogous chiral reagent derived from aliphatic aldehydes was developed …”
Section: “Active Aldehyde” Equivalents In Asymmetric Synthesismentioning
confidence: 99%
“…In their synthesis of the lignans (+)-hinokinin and cubebin dimethyl ether, Enders and Milovanovic used the vinylogous addition of the Strecker product obtained from auxiliary 217 and piperonal to 5H-furan-2-one for the installation of the first asymmetric center. 214,215 The product was obtained in >98% diastereomeric excess and was subsequently a-alkylated with piperonyl bromide to furnish the trans-configured 2,3-disubstituted butanolide 220, again in high diastereoselectivity. 216 Removal of the chiral auxiliary under formation of the aryl ketone with aqueous silver nitrate and reductive removal of the carbonyl group in a reduction-hydrogenation sequence yielded (+)-hinokinin (222), which could be converted into (S,S)- cubebin dimethyl ether (223) by reduction and O-methylation (Scheme 39).…”
Section: Scheme 38 Asymmetric Synthesis Of 14-dicarbonyl Compounds Bmentioning
confidence: 99%
“…Another deprotonation-alkylation sequence in combination with the reductive removal of the nitrile function by sodium in liquid ammonia gave T-8, while its diastereomer T-7 was obtained by Bruylants reaction of 210 with n-pentylmagnesium bromide (Scheme 36). 207 The synthesis of the tropane alkaloid ferruginine (215), an agonist of the nicotinic acetylcholine receptor that was isolated from the bark of the arboreal species Darlingiana ferruginea, was achieved starting from 207. 208 In contrast to 206, its higher homologue, this material is conveniently prepared and used as an inconsequential epimeric mixture.…”
mentioning
confidence: 99%